In vitro evaluation of the fracture strength of all-ceramic core materials on zirconium posts - Ozcan, Nihal; Sahin, Erdal (European Journal of Dentistry, 2013)
Objective: For most endodontically treated teeth, tooth-colored post-core systems are preferable for esthetic reasons. Therefore, improvements in material strength must also consider tooth colored post-core complexes. The objective of this study was to evaluate the difference in tooth colored post-core complex strengths. Materials and Methods: A total of 33 human maxillary central incisor teeth were used for this study, with three groups of 11 teeth. Three different methods were used to fabricate all-ceramic post-core restorations: zirconia blanks, Cerec 3D-milled to one-piece post-core restorations (Test Group 1); feldspathic cores (from feldspathic prefabricated CAD/CAM blocks) adhesively luted to CosmoPost zirconia posts (Test Group 2); and IPS Empress cores directly pressed to CosmoPost zirconia posts (Test Group 3). All-ceramic crowns from feldspathic ceramic were constructed using a CAD/CAM system (Cerec 3D) for all specimens. The post-core complexes were tested to failure with the load applied at 45° angled relative to the tooth long axis. The load at fracture was recorded. Results: The maximum fracture strength of the milled zirconia cores (Test Group 1) was 577 N; corresponding values for the milled feldspathic cores (Test Group 2) and the pressed cores (Test Group 3) were 586 and 585 N, respectively. Differences were not statistically significant at P < 0.05 (P = 0.669). Conclusions: All-ceramic cores adhesively luted on zirconia posts and one-piece all-ceramic zirconium post-core structures offer a viable alternative to conventional pressing.
Keywords: All-ceramic crown; all-ceramic post-core; one-piece post-core; zirconium post-core